2015
DOI: 10.1111/apa.12864
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive outcome varies in adolescents born preterm, depending on gestational age, intrauterine growth and neonatal complications

Abstract: AimThe aim of this study was to investigate long-term cognitive outcome in a cohort of 18-year-olds born preterm and previously assessed at the age of 5.5.MethodsWe tested 134 adolescents born preterm with a very low birthweight of <1500 g and 94 term-born controls with a comprehensive cognitive battery at 18 years of age. The cohort was subdivided into 73 extremely preterm, 42 very preterm and 19 moderately preterm infants with gestational ages of 23–27, 28–31 and 32–36 weeks, respectively. The moderately pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
52
2
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 34 publications
3
52
2
3
Order By: Relevance
“…1,2,6,18,33 Corresponding deficits among ELGAN participants across measures of attention, executive control, and processing speed as well as visual perception and fine motor control were also comparable to those reported for earlier cohorts. 4,6,14,34 Our findings indicate that schoolaged children born extremely preterm continue to be at significant risk of a wide range of neurocognitive and academic deficits.…”
Section: Neurocognitive and Academic Outcomes Among Elgan Participantmentioning
confidence: 72%
See 2 more Smart Citations
“…1,2,6,18,33 Corresponding deficits among ELGAN participants across measures of attention, executive control, and processing speed as well as visual perception and fine motor control were also comparable to those reported for earlier cohorts. 4,6,14,34 Our findings indicate that schoolaged children born extremely preterm continue to be at significant risk of a wide range of neurocognitive and academic deficits.…”
Section: Neurocognitive and Academic Outcomes Among Elgan Participantmentioning
confidence: 72%
“…Extremely preterm children are at heightened risk of deficits in IQ, [1][2][3][4][5][6] attention, 7,8 executive function, 4,6,[9][10][11][12][13][14] processing speed, [15][16][17] visual perception, 6,14 and visual-motor function. 6,14 Neurocognitive deficits are accompanied by delays in academic attainment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Participant characteristics are displayed in Table 1. The cohort, attrition analyses, and assessments have been presented in greater depth in previous articles (Böhm, Katz-Salamon, Smedler, Lagercrantz, & Forssberg, 2002;Lundequist et al, 2015).…”
Section: Participantsmentioning
confidence: 99%
“…Comprehensive neuropsychological assessments were conducted at age 5.5 and 18 years. From this cohort, we have previously reported that executive function was a specific weakness at 5.5 years and remained so still at 18 years (Böhm, Smedler, & Forssberg, 2004;Lundequist et al, 2015). We now seek to further investigate executive function development in this cohort, leaning on Miyake and Friedman's theoretical model (2012) and the empirical support lent to it by Huizinga and colleagues (2006).…”
mentioning
confidence: 92%